Premalignant Lesions in the Kidney - Ziva Kirkali; Kutsal Yorukoglu (The Scientific World Journal)
Renal cell carcinoma (RCC) is the most malignant urologic disease. Different lesions, such as dysplasia in the tubules adjacent to RCC, atypical hyperplasia in the cyst epithelium of von Hippel-Lindau syndrome, and adenoma have been described for a number of years as possible premalignant changes or precursor lesions of RCC. In two recent papers, kidneys adjacent to RCC or removed from other causes were analyzed, and dysplastic lesions were identified and defined in detail. Currently renal intraepithelial neoplasia (RIN) is the proposed term for classification. The criteria for a lesion to be defined as premalignant are (1) morphological similarity; (2) spatial association; (3) development of microinvasive carcinoma; (4) higher frequency, severity, and extent then invasive carcinoma; (5) progression to invasive cancer; and (6) similar genetic alterations. RIN resembles the neoplastic cells of RCC. There is spatial association. Progression to invasive carcinoma is described in experimental cancer models, and in some human renal tumors. Similar molecular alterations are found in some putative premalignant changes. The treatment for RCC is radical or partial nephrectomy. Preneoplastic lesions may remain in the renal remnant in patients treated by partial nephrectomy and may be the source of local recurrences. RIN seems to be a biologic precursor of some RCCs and warrants further investigation. Interpretation and reporting of these lesions would reveal important resources for the biological nature and clinical significance. The management of RIN diagnosed in a renal biopsy and partial nephrectomy needs to be answered.